TOXIC RELATIONSHIP SEBAGAI DASAR PERCERAIAN: ANALISIS KEKERASAN PSIKIS DALAM HUKUM KELUARGA ISLAM DAN UU PKDRT - wahyu (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study aims to analyze divorce caused by toxic relationships as a form of psychological violence within the framework of Islamic family law and its relevance to Law Number 23 of 2004 concerning the Elimination of Domestic Violence (UU PKDRT). This research employs a qualitative approach through library research using primary sources such as classical Islamic jurisprudence texts, religious court decisions, and statutory regulations, supported by secondary sources including books and scholarly articles. The data were analyzed descriptively and analytically through a normative-sociological approach. The findings show that psychological violence in toxic relationships constitutes darar ma‘nawi, which contradicts the principles of mu‘asyarah bi al-ma‘ruf and the objectives of maqasid al-syari‘ah. Decisions from the Religious Courts of Jember and Malang demonstrate that judges increasingly consider emotional harm and mental suffering as legitimate grounds for divorce, aligning with the provisions of UU PKDRT. This study highlights the convergence between Islamic jurisprudence and positive law in protecting victims of non-physical violence and underscores the need to strengthen legal understanding and evidentiary mechanisms that are responsive to psychological abuse.